Aplikasi Sistem Informasi Geografis pada Pemantauan Status Gizi Balita di Dinas Kesehatan Kabupaten Sukoharjo - Mutalazimah, M; Handaga, Bana; Sigit, Agus Anggoro (Forum Geografi, 2009)
The research was conducted to develop the information system model on nutrition status of child monitoring based on geographical information system (GIS) to support the plan of increasing the nutrition improvement at the District Health Office, Sukoharjo Regency. This descriptive research was carried out by implementing interview to subjects who were involved in the activity of the monitoring. Observation was also performed to two objects, namely the structure and the procedure of information. The collected data were analyzed descriptively by applying result of structure and the procedure analysis. The system development was designed by using the approach of FAST (Framework for the Application of System Techniques). The observation to the problem, scope, and property had been conducted by the interview with the subjects indicate that the research subjects at all levels from top managers to persons in the transactional level as well as those who are at cross section department support the development of monitoring system to the improvement of nutrition status program, and this system is reliable to mapping perform of nutrition status of child based on the category as severe malnutrition, under nutrition, normal and overweight. In the future nutrition information based on GIS have the benefits of the new system in supporting the monitoring activity toward the nutrition improvement program and it also supports the plan. Suggestions from this research might go to the government health institution to develop spatial or terrestrial data on the health programs have to be designed GIS for the each other program. Moreover, the other model should be developed GIS in the other spatial data and information can be accessed by informative map.